Antioxidant Test Of Granola Bar Functional Food With Cork Fish And Beetroot (Beta Vulgaris L) As Supplementary Food To Prevent Stunting - Pradana, Riska; Septiana Laksmi Ramayani (Media Farmasi Indonesia, 2025)
Stunting generally occurs in children who have not received nutritious food intake. Sources of nutrition are not only sourced from animal protein but can also be sourced from plants. Combining high-protein foods from animal and vegetable sources will reduce stunting rates in growing children. Snack bars are a beneficial food product that provides all the essential nutrients for the body. In addition, probar consumption in Indonesia is still relatively low, and some people don’t even know it exists. These snacks are high in usable energy and contain essential nutrients. This study aims to determine the free radical-catching activity of Granola Bar Functional Food with Cork Fish and Beetroot Fruit as Supplementary Food to Prevent Stunting. Free radical scavenging activity test was conducted using the DPPH (1,1- diphenyl- 2-picrylhydrazyl) method using quercetin as the comparative compound. Antioxidant activity analysis was performed using a spectrophotometer at a wavelength of 512 nm.